Banggai cardinalfish (Pterapogon kauderni) monitoring in Bokan Kepulauan (2017-2021) highlights the need for the "BCF Garden" approach. Issue 1 (1st January 2023) - Ndobe, S; Serdiati, N; Gani, A; Walalangi, J Y; Moore, A M
Abstract: The Banggai cardinalfish Pterapogon kauderni is a restricted range marine fish classified as Endangered in the International Union for Conservation of Nature Red List. Traded as an ornamental fish, the Banggai cardinalfish (BCF) is of national and international conservation concern. The "BCF Garden" concept aims to replenish depleted BCF stocks through community-based habitat and microhabitat rehabilitation. Under the National Action Plan for Banggai cardinalfish conservation, selected BCF populations have been monitored annually since 2017. Eight endemic BCF populations in the Bokan Kepulauan District, Banggai Laut Regency, Central Sulawesi Province, were monitored using a standardized belt transect method in 2017, 2018, 2019, and 2021. Data were collected on BCF abundance, size/age structure and microhabitat association, and critical microhabitat abundance (sea urchins, mainly Diadema and sea anemones). Despite the inter-site variation, overall abundance declined significantly for BCF ( p = 0.02) and sea urchins ( p =0.02). Total counts of BCF (4646) and urchins (498) in 2021 were 31% and 11%, respectively, of 2017 values (4921 and 4460); sea anemone count increased (61 to 87) but remained well below historical abundance levels. These results confirm the need for targeted measures to promote the recovery of BCF populations in Bokan Kepulauan. The holistic BCF Garden approach is recommended, especially at sites where Diadema urchins are heavily exploited.